Majoritarian tendency and semi-presidential regime in Indonesia - Arry Bainus, Gunawan Suswantoro, Muradi,; Amali, Zainudin (Opción, 2019)
This paper analyzed the majoritarian tendency effects of the coming into effect of the semi-presidential regime in the administration of the president SBY-Boediono and the Jokowi-JK government via qualitative analysis through in-depth interviews. As a result, characteristics of semi-presidential regimes in the Indonesian political system resulted in a gridlock of the cabinet coalition and the Semi Presidency creates a new harmonization in the construction of relationships between the executive and the legislature. In conclusion, the long process of the journey of democratization will face trials with the nature of the national political system with its various good oligarchy.